PENGARUH IMPLEMENTASI KEBIJAKAN ANGGARAN PENDAPATAN DAN BELANJA DESA TERHADAP KEBERHASILAN PEMBANGUNAN DI DESA KUSU LOVRA KECAMATAN KAO KABUPATEN HALMAHERA UTARA - NGANGANGOR, RISKY PAUL; POSUMAH, JOHNNY HANNY; SONDAKH, TELLY (Sam Ratulangi University, 2014)
ABSTRACT :This study questioned the fundamental problems, namely: the extent of theinfluence of policy implementation Budget Village (APBDes) the success of developmentin the village of Lovra Kusu District of North Halmahera Kao? Thus, this researchaims: to determine the extent of the effect of policy implementation Budget Village(APBDes), the success of Rural Development in Kusu Lovra Kao District of NorthHalmahera.This empirically using a quantitative approach to the application of descriptive andexplanatory methods. The data and information collected through questionnairesdistributed technique to 50 respondents, and is equipped with observation anddocumentation, then analyzed by applying techniques prosuct moment correlationanalysis and simple linear regression.Based on the results of data analysis, it is known that the success of the implementationAPBDes and Rural Development in the Rural District of Kao Kusu Lovra NorthHalmahera in the category